Next-Generation CAR-T Cells for HIV Cure Strategies: Dual-Specific Chimeric Antigen Receptors for Targeted Elimination of Latent Reservoirs Toward Artificial, Durable, and Adaptive Immune Surveillance - Barack Ndenga (Publisher, 2026)
Despite the transformative success of antiretroviral therapy (ART), HIV-1 persists as a lifelong infection due to the establishment of long-lived latent reservoirs. These reservoirs remain immunologically silent and pharmacologically inaccessible, representing the principal barrier to viral eradication. In this analysis, I explore how recent advances in cellular immunotherapy—particularly chimeric antigen receptor T (CAR-T) cell technology—offer a paradigm shift from passive viral suppression to active, programmable immune surveillance. I focus on the emergence of next-generation, dual-specific CAR-T cells engineered to recognize and eliminate HIV-infected cells, including those emerging from latency. I examine the molecular design principles, antigen selection strategies, safety engineering, and translational challenges that position CAR-T-based approaches as a cornerstone of future functional or sterilizing HIV cure strategies. Keywords : HIV cure,CAR-T cells,Latent reservoir,Cellular immunotherapy,Synthetic immunity,Dual-specific CAR,Chimeric antigen receptor,Logic-gated CAR,Shock and Kill,Immune surveillance,HIV persistence,Immune evasion,Adoptive cell transfer,Translational medicine,Combination therapy
The persistence of latent HIV reservoirs, invisible to the immune system and antiretroviral drugs, remains the definitive barrier to a cure. In this article, I explore a paradigm shift from passive viral suppression to active, programmable immune surveillance using engineered chimeric antigen receptor T (CAR-T) cells. I focus on the design and strategic application of next-generation, dual-specific CAR-T cells capable of recognizing conserved viral and host-derived markers to precisely eliminate HIV-infected cells emerging from latency. By examining molecular architectures, safety mechanisms, and their role within combinatorial cure strategies, I position these synthetic immune cells as a cornerstone for developing functional or sterilizing HIV cure interventions. This work frames advanced cellular immunotherapy not merely as a treatment, but as the foundation for durable, artificial immune surveillance.